A GICA strip for Campylobacter jejuni real-time monitoring at meat production site. (December 2018) - Zang, Xiaoqi; Kong, Ke; Tang, Haiyan; Tang, Yuanyue; Tang, Hong; Jiao, Xinan; Huang, Jinlin
Abstract: Campylobacter jejuni ( C. jejuni ) contamination occurs vastly and inevitably at the meat production site, which makes the real-time monitoring of C. jejuni an increasingly key part for the food safety control. Aiming to establish a C. jejuni on-site detection method, a colloidal gold immunochromatographic assay (GICA) was developed with a visual lowest detection limit of 10 2  CFU/μL of C. jejuni . Although the larger volume of antigen (bacteria) increased the difficulty of research, the developed GICA allowed a 10-min monitor of C. jejuni in pork samples at the production site with an accuracy of 93%, compared with traditional culture method. By analysing samples with the different cleanliness, both the specificity (0.94) and the accuracy (0.88) of meat samples versus culture were higher than those from fecal samples. By monitoring samples with a series of C. jejuni carriage loads, GICA performed more sensitive in pork samples, which both the specificity (0.98) and the accuracy (0.93) were higher than those in chicken meat samples. The developed GICA is a more portable and practical method for C. jejuni detection without the bacterial cultivation, which can provide a technical assistance for the real-time detection and the hazard control of C. jejuni in meat production. Highlights: A try of C. jejuni GICA strip conquering the difficulty of macromolecular detection. Preparation of a GICA strip for C. jejuni real-time monitor at meat production site. The GICA strip was more sensitive for monitoring samples with high cleanliness. The assay was more sensitive for monitoring samples with low C. jejuni carry loads.